(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2018)
Backgroud : Pain management is an universal concern for women during labour. Ideal labour analgesia should effectively reduce the pain and have minimal adverse effects on the fetus and progress of labour. Materials and methods : The present cross sectional comparative study was carried out in the Department of Obstetrics and Gynecology, Chittagong Medical College Hospital (CMC&H) between January 2014 and July 2014 to compare the efficacy and safety between epidural analgesia and opioid analgesia on nulliparous women in labour. In this study, study population were Pregnant women with labour pain admitted in the Department of Obstetrics and Gynaecology, CMC&H. Samples were selected following inclusion and exclusion criteria. Then randomization was done to divide them in groups, group A & B each having 40 patient. Group A received epidural analgesia at the L3-4 interspace with 0.125% Bupivacaine 10 ml and Fentanyl 50 mg & group B received opioid analgesia (Inj. Pethidine and Phenargon). Then the subjects were followed up and outcome were recorded in a preformed data collection sheet. All data were analyzed by computer based software SPSS version 15. Quantitative data was analyzed by Student’s t- test. Categorical variables were analyzed by Chi square (c2) test & Fisher’s Exact Test. Results : Statistical significance was set at P value less than <0.05 and confidence interval set at 95% level. The two groups were almost identical with respect to maternal age, gestational age and pre-induction pain score (p = 0.127, p = 0.454 and p = 0.186 respectively). The onset of analgesia in epidural group was significantly earlier than that in the opioid group. The pain score at onset and at different time intervals following induction and at the time of delivery were appreciably lower in women receiving epidural analgesia with Bupivacaine 0.125% and Fentanyl than those receiving opioid analgesia with Pethidine & Phenargon injection (p < 0.001). In terms of the complications like nausea and/or vomiting there was no significant difference between the epidural and the opioid groups (p = 0.431). Four (10.0%) patients in the epidural group experienced prolonged 2nd stage of labour compared to none in the opioid group (p = 0.027). Majority of the patients in either group have had normal delivery. Only 2 (5%) patients in the epidural group and 5 (12.5%) in the opioid group required caesarean delivery and 4 (10.0%) patient in the former group and 1 (2.5%) patient in later group required instrumental delivery (p = 0.455). Fetal distress was primarily the indication for caesarean delivery in either group (p = 0.310). Instrumental delivery in the epidural group was required due to prolonged 2nd stage of labour and in opioid group due to fetal distress in 2nd stage of labour (p = 0.027). No significant differences was observed between the epidural and opioid analgesia groups in terms of APGAR scores at 1 and 5 minutes of birth (p = 0.401 and p = 0.536 respectively). Conclusion : The study concluded that epidural analgesia with Bupivacaine induces a much earlier onset of analgesia than does the opioid analgesia with Pethidine & Phenargon injection. The intensity of pain was dramatically reduced to a tolerable level following epidural analgesia and was maintained at this level up to delivery. There was no significant difference in complications between the epidural and opioid groups. JCMCTA 2017 ; 28 (2) : 21-26